SARS-CoV-2 Infection Among Health Care Workers Despite the Use of Surgical Masks and Physical Distancing—the Role of Airborne Transmission. (27th January 2021) - Goldberg, Lotem; Levinsky, Yoel; Marcus, Nufar; Hoffer, Vered; Gafner, Michal; Hadas, Shai; Kraus, Sraya; Mor, Meirav; Scheuerman, Oded
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted mainly via respiratory droplets. A key question in the coronavirus disease 2019 pandemic is whether SARS-CoV-2 could be transmitted via the airborne route as well. We report for the first time SARS-CoV-2 nosocomial infections despite using surgical masks and physical distancing. This report may provide possible evidence for airborne transmission of SARS-CoV-2. Abstract : SARS-CoV-2 is transmitted mainly via respiratory droplets. We report for the first time SARS-CoV-2 nosocomial infections, despite using surgical masks and physical distancing. It may provide a possible evidence for airborne transmission of the virus.